Review: Potential production of carotenoids from Neurospora - SRI PRIATNI (Smujo International, 2014)
Abstract. Priatni S. 2014. Review: Potential production of carotenoids from Neurospora. Nusantara Bioscience 6: 63-68. Carotenoids are abundant and widely distributed in plants, animals, and microorganisms. Commercial use of carotenoids competes between microorganisms and synthetic manufacture. Carotenoids production can be increased by improving the efficiency of carotenoid synthesis in microbes. Some of the cultural and environmental stimulants are positively affecting the carotenoid content of carotenogenic strains such as Neurospora. Neurospora is a fungus that exhibits the formation of spores and conidia, the part of the cell for carotenoids biosynthesis. The Indonesian traditional fermented food, red peanut cake or oncom, especially in West Java, is produced from legume residues of Neurospora sp. This fungus has been isolated and identified as Neurospora intermedia. In order to apply this pigment for food and cosmetic colorants, encapsulation techniques of carotenoids have been developed to improve its solubility and stability.